Central American years in Costa Rica - Rojas, Margarita (2021)
Costa Rican arts and culture grew and spread in a special way during the 1970s. This situation was combined with the integration of many Latin American artists and intellectuals who came to the country in exile due to dictatorships and wars in their countries. This article attempts to synthesize the partial information that exists on those years and at the same time study the new Central Americanism that developed then in the form of a struggle for democracy and solidarity among the peoples of the Isthmus.